Simulating personal income tax in South Africa using administrative data and survey data: A comparison of PITMOD and SAMOD for tax year 2018 - Wynnona Steyn; Alexius Sithole; Winile Ngobeni; Eva Muwanga-Zake; Helen Barnes; Michael Noble; David McLennan; Gemma Clare Wright; Katrin Gasior (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
In this paper we explore South Africa's personal income tax system using two microsimulation models. The first, SAMOD, simulates personal income tax and social benefits using a dataset derived from the nationally representative National Income Dynamics Study survey. The second, PITMOD, simulates the personal income tax system and is underpinned by a dataset comprising a full extract of anonymized individual-level administrative tax data especially constructed for this purpose. The two models have a common framework in the form of the EUROMOD microsimulation software and interface, and have a common policy timepoint of 1 March 2017. Discrepancies between the simulated personal income tax generated by each model are explored in order to better understand the strengths and weaknesses of the two models.
Keywords: C63; C81; D31; H24; 330; microsimulation; personal income tax; income distribution; South Africa